Solving the updated and downdated ordinary linear model on massively parallel simd systems - Kontoghiorghes, Erricos John; Clarke, M. R. (My University, 1993)
Several algorithms have appeared for solving the Ordinary Linear Model (OLM), after a number of observations have been added or deleted. In this paper we employ Householder transformations and Givens rotations to solve the updated and downdated OLM, using a massively parallel SIMD computer. Some of our methods are modified versions of serial algorithms published previously while others appear for the first time. The execution time models of all algorithms are studied and compared.
Keywords: Givens rotations; Householder transformations; Ordinary linear model; Parallel algorithms